Evaluation Research as a Mechanism for Critical Inquiry and Knowledge Construction in Architectural and Urban Education - Salama, Ashraf M. (FormAkademisk, 2012)
This paper responds to the misconceptions that continue to characterize the delivery of knowledge content in architectural courses. Based on reviewing the literature on pedagogy, the paper explores the value and benefits of introducing evaluation research as a mechanism for critical inquiry and knowledge construction in theory courses in architecture and urbanism. A framework is developed and employed to demonstrate how this type of learning can be incorporated. The development and implementation of a series of in-class and off-campus exercises in two different contexts reveal that structured actions and experiences help students control their learning experience while invigorating their understanding of the knowledge delivered in a typical lecture format. It firmly believed this would offer students multiple learning opportunities while fostering their capabilities to shift from passive listeners to active learners and from knowledge consumers to knowledge producers.